1995
DOI: 10.1016/0006-3223(94)00297-g
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin production in vitro in major depression: A pilot study on the modulating action of endogenous cortisol

Abstract: To investigate the possible differential sensitiviO' of hydrocortisone (HCO) on immunoglobulin (Ig) production in depression in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In this study, AlCl 3 decreased IgG production, suggested that AlCl 3 inhibited humoral immune. Hydrocortisone, a kind of GCs, stimulated immunoglobulin production at concentration of 10 −8 mol/L and inhibited at concentration of 10 −5 mol/ L in peripheral blood lymphocytes from humans [46]. In this study, 10 −8 mol/L Cort stimulated IgG production and 10 −6 mol/L inhibited IgG production.…”
Section: Discussionsupporting
confidence: 50%
“…In this study, AlCl 3 decreased IgG production, suggested that AlCl 3 inhibited humoral immune. Hydrocortisone, a kind of GCs, stimulated immunoglobulin production at concentration of 10 −8 mol/L and inhibited at concentration of 10 −5 mol/ L in peripheral blood lymphocytes from humans [46]. In this study, 10 −8 mol/L Cort stimulated IgG production and 10 −6 mol/L inhibited IgG production.…”
Section: Discussionsupporting
confidence: 50%
“…In fact, previous studies carried out in humans or laboratory animals under a large variety of experimental conditions have demonstrated that when adrenocortical activity is intense, T-cell activity is depressed and B-cell activity is elevated (MacMurray et al 1983;Kok et al 1995;Elenkov and Chrousos 1999;Moynihan 2003). In particular, Elenkov and Chrousos (1999) indicated that under stressful conditions, glucocorticoids may suppress cellular immunity and boost humoral immunity via an effect on T helper 1 (Th1)/Th2 cells and type 1/type 2 cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…This is more pronounced in elderly caregivers who are under chronic stress [25]. Furthermore, lymphocytes from persons under chronic depression (stress) become resistant to the immunosuppressive effect of steroids [26]. This was reported in depressive patients in whom chronically high cortisol levels are noticed [27].…”
Section: Psychoimmunology Of Nutritionmentioning
confidence: 94%